Ontogeny in the European earwig (Forficula auricularia) and grain crops interact to exacerbate feeding damage risk. (4th August 2020) - Kirkland, Lisa S.; Maino, James; Stuart, Oliver; Umina, Paul A.
Abstract: The preference of herbivores for different host plants can be modulated by plant ontogeny. In agricultural pest management, this has implications for sowing dates and pest monitoring. In the last 20 years, the European earwig ( Forficula auricularia ), a cosmopolitan pest, has been increasingly implicated in damage to grain crops in Australia. Among these, rapeseed, Brassica napus, appears especially at risk, but little information on F. auricularia as a grain pest is available. We tested the susceptibility of seven grain crops commonly grown in Australia to infestation by F. auricularia using closed microcosm experiments, exposing plant seedlings at two early growth stages to four different life stages of F. auricularia . Lucerne and rapeseed were shown to be the most vulnerable crops, and younger seedlings experienced significantly more damage than older seedlings across all crop types. Fourth instar F. auricularia were found to cause greater feeding damage than younger or older earwigs, while adults collected in winter generally caused more damage than those collected in summer. Surprisingly, even second instar F. auricularia caused greater damage than summer adults. This variation could reflect the ontogenetically dynamic nutritional needs of earwigs. Recent studies of F. auricularia 's life cycle in southern Australia indicate that these damaging life stages have some overlap with sowing dates of the crops tested here, exposing their vulnerable seedling stage to infestation. The phenology of F. auricularia in southern Australia therefore partly drives its ability to act as a pest. Future monitoring will likely need to track the distribution of F. auricularia life stages in order to effectively mitigate risks to vulnerable crops.